ChemInform Abstract: Copper‐Catalyzed Olefinic C—H Difluoroacetylation of Enamides. Issue 40 (30th September 2014) - Caillot, Gilles; Dufour, Jeremy; Belhomme, Marie‐Charlotte; Poisson, Thomas; Grimaud, Laurence; Pannecoucke, Xavier; Gillaizeau, Isabelle
Abstract The regioselective Cu‐catalyzed radical free synthesis of β‐difluoroester substituted enamides is described.